Use of Gloves for the Prevention of Covid-19 in Healthy Population: A Living Systematic Review Protocol - Duarte-Anselmi, G (John Wiley and Sons Inc, 2021)
Background and aims: The efficacy of using gloves by the general population to prevent COVID-19 is unknown. We aim to determine the efficacy of routine glove use by the general healthy population in preventing COVID-19. This is the protocol of a living systematic review. Methods: We adapted an already published common protocol for multiple parallel systematic reviews to the specificities of this question. We will conduct searches in PubMed/Medline, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), grey literature, and in a centralized repository in L·OVE (Living OVerview of Evidence). L·OVE is a platform that maps PICO questions to evidence from Epistemonikos database. In response to the COVID-19 emergency, L·OVE was adapted to expand the range of evidence it covers and customized to group all COVID-19 evidence in one place. The search will cover the period until the day before submission to a journal. We will include randomized trials evaluating the effect of use of gloves in healthy population to prevent COVID-19 disease. Randomized trials evaluating the effect of use of gloves during outbreaks caused by MERS-CoV and SARS-CoV, and nonrandomized studies in COVID-19 will be searched in case no direct evidence from randomized trials is found. Two reviewers will independently screen each study for eligibility, extract data, and assess the risk of bias. We will perform random-effects meta-analyses and use GRADE to assess the certainty of the evidence for each outcome. A living, web-based version of this review will be openly available during the COVID-19 pandemic. We will resubmit it if the conclusions change or there are substantial updates. © 2021 The Authors. Health Science Reports published by Wiley Periodicals LLC.